2013
DOI: 10.1007/s00248-013-0248-6
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Biodegradation of 2,4,6-Trinitrotoluene (TNT) by Bacillus cereus İsolated from Contaminated Soil

Abstract: In this study, biological degradation of 2,4,6-trinitrotoluene (TNT) which is very highly toxic environmentally and an explosive in nitroaromatic character was researched in minimal medium by Bacillus cereus isolated from North Atlantic Treaty Organization (NATO) TNT-contaminated soils. In contrast to most previous studies, the capability of this bacteria to transform in liquid medium containing TNT was investigated. During degradation, treatment of TNT was followed by high-performance liquid chromatography (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 35 publications
6
27
0
Order By: Relevance
“…Many studies have discussed the synthesis of nitro-aromatic explosives such as 2,4,6-trinitrotoluene (TNT) and 2,4,6-trinitrophenol (picric acid) and their uses for military purposes because of their highly explosive properties, thermal stability, and their insensitivity to shock and friction [8,9]. In civilian industries, these compounds are used as raw materials for the manufacturing of pesticides, herbicides, pharmaceutical products, dyes, and explosives [10,11]. Thus, the extensive use of these explosives in military applications requires the implementation of extensive handling and disposal techniques, whereas their transformation products lead to increased environmental pollution-particularly in the soil, sediment, surface, and groundwater-to levels that threaten human health and the environment [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have discussed the synthesis of nitro-aromatic explosives such as 2,4,6-trinitrotoluene (TNT) and 2,4,6-trinitrophenol (picric acid) and their uses for military purposes because of their highly explosive properties, thermal stability, and their insensitivity to shock and friction [8,9]. In civilian industries, these compounds are used as raw materials for the manufacturing of pesticides, herbicides, pharmaceutical products, dyes, and explosives [10,11]. Thus, the extensive use of these explosives in military applications requires the implementation of extensive handling and disposal techniques, whereas their transformation products lead to increased environmental pollution-particularly in the soil, sediment, surface, and groundwater-to levels that threaten human health and the environment [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In a study published by Gümüşçü and Tekinay [6], it was determined that the amounts of TNT in soil and water samples taken from Elmadağ region of Ankara was in the range of 20-245 mg/ kg. In another study published by Mercimek et al [17], the amount of TNT in the sample taken from the NATO region in Izmir, Turkey was determined as 61.35 mg/L. The amount of TNT in the water sample taken for bacterial isolation was determined to be 134 mg/kg and TNT contamination of the sample was found to be between the limits specified in the literature.…”
Section: Isolation and Identification Of Microorganismsmentioning
confidence: 81%
“…SU K3 and SU K4 isolates had high TNT degradation capacity compared to SU K2 and it was determined that the isolates degraded 96 % and 93 % of the initial TNT respectively at the end of the 24-h incubation period. Since, the isolates were selected according to their ability, the resulting bacterial isolates increased cell biomass in the presence of 100 mg/L TNT and degraded the initial TNT at rates ranging from 70 % to 96 % within 24 h. Compared to previous TNT degradation studies in the literature, these degradation rates were observed to be quite high [17,30].…”
Section: Tnt Degrading Experimentsmentioning
confidence: 99%
“…Many microbes, including Escherichia coli [6][7][8], Enterobacter cloacae [9], Bacillus cereus [10], Clostridium acetobutylicum [11], Clostridium thermoaceticum [12], Klebsiella sp. C1 [13], Phanerochaete chrysosporium [14], Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%